Seminoma of Testis Masquerading as Orchitis in an Adult with Paraplegia: Proposed Measures to Avoid Delay in Diagnosing Testicular Tumours in Spinal Cord Injury Patients - Subramanian Vaidyanathan; Peter L. Hughes; Paul Mansour; Bakul M. Soni (The Scientific World Journal)
Orchitis is common in adult male spinal cord injury (SCI) patients and, therefore, both health professionals and SCI patients themselves tend to attribute testicular swelling to orchitis, with a consequent potential delay in the diagnosis of testicular tumours. A 37-year-old man with paraplegia developed swelling of the right testis. With a presumptive diagnosis of acute bacterial orchitis, he was prescribed ciprofloxacin while awaiting an ultrasound scan. Ultrasound examination of the testis 4 weeks later showed a moderate hydrocele, enlargement and altered echogenicity of both the epididymis and testis, and features of mass-like lesions within the substance of the testis. As these changes might merely have represented a partly treated infection, a follow-up scan was carried out 2 weeks later, which revealed a lobulated mass of mixed echogenicity within the testis and a focal area of increased echogenicity indicative of calcification. A radical orchidectomy performed 19 days later revealed a seminoma. To prevent delay in the diagnosis of testicular tumours in SCI patients, we propose the following measures: (1) patients who develop swelling of the testis should consult a physician as soon as possible for clinical examination; blind antibiotic therapy should be avoided if possible; (2) if clinical examination reveals a hard swelling of the testis and the typical features of acute urinary infection are absent, an ultrasound scan of the scrotum should be performed as soon as possible; (3) in patients with equivocal ultrasound findings, ultrasound-guided, fine-needle aspiration cytology may allow an early diagnosis of testicular malignancy; (4) education of SCI patients and their caregivers is needed to implement these recommendations.